PENGARUH KETERLIBATAN ORANG TUA TERHADAP PERKEMBANGAN KETERAMPILAN MEMBACA DAN MENULIS ANAK USIA DINI - Mukhlisoh, Lilis; Sari, Novita; Yuliadi, Desma (Jurnal Anak Bangsa, 2024)
This research was motivated by the large number of parents who hoped that children attending PAUD Al-Munawaroh would be able to read and write. Parents demand that teachers always teach reading and writing compared to activities that can train children's focus. Meanwhile, parents forget their role in providing reading and writing lessons at home. This research aims to analyze the level of parental involvement in developing early childhood reading and writing skills at PAUD Al-Munawaroh. This research uses quantitative with a descriptive approach. The data collection technique uses a questionnaire which will be distributed to 40 samples. By distributing questionnaires online via Google Form and offline via distributing questionnaires. The data analysis technique in this research uses descriptive statistics by looking for data validation, highest score, lowest score, mean value and standard deviation. The place where the research was carried out was Al-Munawaroh PAUD which is located at Kp. Laban Ds. Laban RT/RW. 005/002 District. Tirtayasa District. Attack Prov. Banten and will be carried out from 21 June to 26 July 2024. The research results showed that parental involvement was high, namely 45% for 18 parents. This can be seen from the questionnaires distributed that parents at Al-Munawaroh PAUD often accompany, pay attention and even teach children about reading and writing skills